2016
DOI: 10.3390/cancers8100094
|View full text |Cite
|
Sign up to set email alerts
|

Mreg Activity in Tumor Response to Photodynamic Therapy and Photodynamic Therapy-Generated Cancer Vaccines

Abstract: Myeloid regulatory cells (Mregs) are, together with regulatory T cells (Tregs), a dominant effector population responsible for restriction of the duration and strength of antitumor immune response. Photodynamic therapy (PDT) and cancer vaccines generated by PDT are modalities whose effectiveness in tumor destruction is closely dependent on the associated antitumor immune response. The present study investigated whether the immunodepletion of granulocytic Mregs in host mice by anti-GR1 antibody would improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Contrastingly, neutrophil presence at the 4 h timepoint may be detrimental. In a previous study, Gr‐1 + cells found beyond the 1 h timepoint were associated with immunosuppressive functions . Referred to as Mregs by these researchers, the cell markers are comparable to that of the modern definition of myeloid‐derived suppressor cells.…”
Section: Discussionmentioning
confidence: 70%
“…Contrastingly, neutrophil presence at the 4 h timepoint may be detrimental. In a previous study, Gr‐1 + cells found beyond the 1 h timepoint were associated with immunosuppressive functions . Referred to as Mregs by these researchers, the cell markers are comparable to that of the modern definition of myeloid‐derived suppressor cells.…”
Section: Discussionmentioning
confidence: 70%
“…Another example is the combination of MEK inhibitor and anti‐PD‐L1 agent. In this approach, MEK inhibition induces intratumor T‐cell accumulation and immune checkpoint inhibition could synergistically upregulate MHC‐I in mouse models followed by the promotion of durable tumor regression (Korbelik, Banáth, & Zhang, 2016; Wei et al, 2014). A preliminary clinical trial in patients with MSS nonhyper‐mutated CRC showed early signs of efficacy using this combination therapy.…”
Section: Potential Combination Therapies With Pd‐1/pd‐l1 Blockadementioning
confidence: 99%
“…Kobayashi et al also reported success in Treg immunodepletion with only IR700 conjugated F(ab′) 2 fragments generated from an anti‐CD25 antibody . Working along similar cell immunodepletion mechanism, the use of anti‐GR1 antibody to target another population of immunosuppressing cells, namely, MDSCs cells provides another avenue to inhibit negative immunoregulatory effects that restricts the strength and duration of antitumor immune response …”
Section: Pdt Cancer Immunotherapymentioning
confidence: 99%